2022
DOI: 10.3390/pr10081496
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Model for Five-Phase Induction Motor Based on Magnetic Noise Reduction Part I: Slot Opening Width

Abstract: Based on the winding function considering the slot width and the air-gap permeability considering the slot opening width, the main radial electromagnetic force wave expressions of the induction motor are determined. The electromagnetic force-vibration prediction model of the induction motor is established. The natural frequency and acoustic radiation model of a finite-length cylindrical shell with two ends clamped is deduced. On this basis, an improved magnetic noise prediction model of cage induction motor is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Chen et al [20] The optimization database of slot opening widths is given for a 30/26 slot five-phase induction motor.…”
Section: Main Advantages Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [20] The optimization database of slot opening widths is given for a 30/26 slot five-phase induction motor.…”
Section: Main Advantages Limitationsmentioning
confidence: 99%
“…When two noise sources produce different SPLs at the same point, that is L P1 6 ¼ 1L P2 . It is troublesome to calculate the total SPL L P according to Equation (20), which can be calculated by Equation (27).…”
Section: Superposition Analysis Of the Electrodynamic Noise And Fluid...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [14,15] proposed an improved magnetic-noise prediction model of a fivephase induction motor through large-slot opening and pole-slot schemes. Luo et al [16] used an extended Kalman filter algorithm for the parameter identification of the five-phase squirrel cage induction motor.…”
Section: Brief Synopsis Of Papers In the Special Issuementioning
confidence: 99%
“…H.S. Chen et al [7], by analyzing the winding function for slot width and the air-gap permeability for slot opening width, found that the main radial force expressions for induction motors were derived and a method was proposed to reduce the noise of the motors without decreasing the drive efficiency and output torque. In Kong et al [8], it is proposed to analyze the electromagnetic vibration under different loads by analyzing the amplitude of electromagnetic force waves.…”
Section: Introductionmentioning
confidence: 99%